Time-dependent Reliability Analysis Method Based on An Explicit Outcrossing Rate in PHI2 - Li, Xiang-Wei; Zhang, Xuan-Yi; Zhao, Yan-Gang; ICASP14 (My University, 2023)
In practical engineering, existing aging structures and infrastructure may suffer from aggressive external load and environmental conditions during their service life, which conditions may cause the deterioration of structural resistance to fall below an acceptable level as specified ones. To analyze and predict the reliability of structure in the whole service period, the development of a time-dependent reliability analysis method is particularly important. PHI2 is one of the most commonly used time-dependent reliability analysis methods, where outcrossing rate is determined by the joint probability with reliability indexes at successive time instants. However, the joint probability is numerical integration essentially, the computational efficiency of which is lower than that of explicit one. To improve efficiency, an explicit outcrossing rate of PHI2 is proposed in this study. Firstly, ourcrossing rate in PHI2 is expressed on the geometric plane with the aid of the definition of outcrossing rate. Secondly, the geometrical relationship of each component is derived from the geometric expression of ourcrossing rate in PHI2. Finally, the explicit outcrossing rate in PHI2 is constructed. The accuracy and efficiency of explicit ourcrossing rate in PHI2 are studied by three numerical examples. The results show that the proposed explicit ourcrossing rate in PHI2 improves the efficiency and keeps accuracy in structural time-dependent reliability analysis.
14th International Conference on Applications of Statistics and Probability in Civil Engineering(ICASP14)
PUBLISHED